EFFECTS OF PROBIOTIC, PREBIOTIC AND SYMBIOTIC ON BROILER BREEDER PERFORMANCE, EGG PRODUCTION AT DIFFERENT STOCK DENSITY - AZIZ, H. I.; AL-Hawezy, D.J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigat the effects of probiotic, prebiotic and symbiotic on the egg production, suitable egg, unsuitable egg and uniformity reread at deferent stock density. A total of 600 broiler breeder Ross 308 (540 female and 60 male) was used in this study for a period of 48 -64 weeks at two levels of stocking density (normal and high stock density). For each stock density birds were fed diet either control diet (T1), standard diet + 0.15g probiotic (Lactobacillus acidophilus, Bacillus subtilis, Bifidobacterium, Saccharomyces cervisiae) powder/ kg diet (T2), standard diet + 0.15g prebiotic (inulin) powder/ kg diet(T3) and standard diet + 0.15g symbiotic (Lactobacillus acidophilus, Bacillus subtilis, Bifidobacterium, Saccharomyces cervisiae+inulin) powder/ kg diet (T4).  Highly significant increase in egg production and suitable egg for dietary additives compared with control group at all weeks of production, but dietary probiotic had significant decrease in unsuitable egg when compared with the controls, however normal density significant increases in egg production and unsuitable egg compared with high density. The probiotic treatments had the lowest body weight variation. It can be concluded that the supplementation of probiotic in the diet of commercial broiler breeder reared under high stocking density had a positive influence on overall suitable egg.